Who Pays for Justice? Perspectives on State Court System Financing and Governance - Geoffrey McGovern, Michael D. Greenberg (RAND Corporation, 2014)
In 2011, the RAND Institute for Civil Justice conducted a broad review of the impact of the financial crisis on the civil justice system. One major area of inquiry involved funding for state courts. Widespread anecdotal accounts suggest that state court funding has significantly dropped from precrisis levels in many parts of the country. Moreover, given broader fiscal problems and trends toward government austerity, it now appears unlikely that lost resources will be restored in the near future. What funding cuts will eventually mean for the function of the state courts, and for litigants who depend on access to those courts, remains to be seen. Subsequently, RAND launched a new study to help understand the variation that exists in the finance and administrative governance of state court systems across the country. Our aim is to investigate and describe state court systems’ funding mechanisms, corresponding elements in the systems’ budgetary accounting, and the systems’ management structure as it relates to generating and spending resources. Such information could be key to understanding what publicly reported budget numbers actually mean for the state courts. In turn, that understanding will be vital to tracking the financial health of state court systems in the future, and to future studies seeking to gauge the impact of judicial branch funding levels on the work that state courts actually carry out. This work should be of interest to policymakers, court administrators, and other stakeholders concerned about ensuring high levels of access to justice through the state courts and the longterm stability of the courts as an institution of government. Previous RAND research in this area yielded the report An Early Assessment of the Civil Justice System After the Financial Crisis: Something Wicked This Way Comes? (Greenberg and McGovern, 2012).